Impact of climate change on farms in smallholder farming systems: Yield impacts, economic implications and distributional effects. (March 2017) - Habtemariam, Lemlem Teklegiorgis; Abate Kassa, Getachew; Gandorfer, Markus
Abstract: The impact of climate change on farms can be determined by factors such as local climatic changes, farm physical environment, the type of crops grown, and household socio-economic characteristics that limit or increase adaptability to climate change. The current study assesses the impacts of climate and socio-economic changes on smallholder farms in two districts of Ethiopia representing different agro-ecology in a major agricultural region. For this purpose, observed farm production data, simulated yield under climate change and socio-economic scenarios were used. The aim was to produce information that facilitates an understanding of the unequal economic implications of climate change on farms. To this end, the study applied the Tradeoff Analysis for Multi-Dimensional impact assessment (TOA-MD) economic simulation model in combination with the AquaCrop yield simulation model. The findings on climate change impact towards 2030 highlight the uneven implications of climate change on farms and the role that agro-ecology and future socio-economic development scenarios play in determining climate change impact. It is found that, under the climate projections we considered crops such as tef, barley and wheat are found to benefit from the projected climate change in cool regions. In warm regions, tef and wheat are projected to be negatively affected whereas maize would benefit. The proportion of farms that are negatively affected by climate change ranged between 51% and 78% in warm regions under different scenarios; in cool regions, the proportion of negatively affected farms ranged between 10% and 22%. The implications of climate change are found to vary under various socio-economic scenarios, in which positive socio-economic scenarios considerably reduced the proportion of negatively affected farms. The economic implications of climate change also found to differ among farms within agro-ecology because of differences in land allocation to various crops that have different sensitivity to climate change, and due to other farm differences. Thus, the study shows the importance of using farm and site-specific production and climate data to reveal variabilities in climate change impact. It also provides evidence on the relevance of accounting for agro-ecology and crop differences as well as consideration of potential socio-economic changes. Overall, the results suggest that appropriate agricultural interventions that recognize location and crop differences are essential to minimize climate change impact. Highlights: TOA-MD model in combination with AquaCrop is used to assess climate change impact. The impact of climate change on yield varied between agro-ecology. The majority of farms in warm regions will be affected by climate change. Farm differences determine the impact of climate change.